Comparison of the diagnostic accuracy of three current guidelines for the evaluation of asymptomatic pancreatic cystic neoplasms. Issue 35 (September 2017) - Xu, Ming-ming; Yin, Shi; Siddiqui, Ali A.; Salem, Ronald R.; Schrope, Beth; Sethi, Amrita; Poneros, John M.; Gress, Frank G.; Genkinger, Jeanine M.; Do, Catherine; Brooks, Christian A.; Chabot, John A.; et al.
Abstract : Abstract: Asymptomatic pancreatic cysts are a common clinical problem but only a minority of these cases progress to cancer. Our aim was to compare the accuracy to detect malignancy of the 2015 American Gastroenterological Association (AGA), the 2012 International Consensus/Fukuoka (Fukuoka guidelines [FG]), and the 2010 American College of Radiology (ACR) guidelines. We conducted a retrospective study at 3 referral centers for all patients who underwent resection for an asymptomatic pancreatic cyst between January 2008 and December 2013. We compared the accuracy of 3 guidelines in predicting high-grade dysplasia (HGD) or cancer in resected cysts. We performed logistic regression analyses to examine the association between cyst features and risk of HGD or cancer. A total of 269 patients met inclusion criteria. A total of 228 (84.8%) had a benign diagnosis or low-grade dysplasia on surgical pathology, and 41 patients (15.2%) had either HGD (n = 14) or invasive cancer (n = 27). Of the 41 patients with HGD or cancer on resection, only 3 patients would have met the AGA guideline's indications for resection based on the preoperative cyst characteristics, whereas 30/41 patients would have met the FG criteria for resection and 22/41 patients met the ACR criteria. The sensitivity, specificity, positive predictive value, negative predictive value of HGD, and/or cancer of the AGA guidelines were 7.3%, 88.2%, 10%, and 84.1%, compared to 73.2%, 45.6%, 19.5%, and 90.4% for the FG and 53.7%, 61%, 19.8%, and 88% for the ACR guidelines. In multivariable analysis, cyst size >3 cm, compared to ⩽3 cm, (odds ratio [OR] = 2.08, 95% confidence interval [CI] = 1.11, 4.2) and each year increase in age (OR = 1.07, 95% CI = 1.03, 1.11) were positively associated with risk of HGD or cancer on resection. In patients with asymptomatic branch duct-intraductal papillary mucinous neoplasms or mucinous cystic neoplasms who underwent resection, the prevalence rate of HGD or cancer was 15.2%. Using the 2015 AGA criteria for resection would have missed 92.6% of patients with HGD or cancer. The more "inclusive" FG and ACR had a higher sensitivity for HGD or cancer but lower specificity. Given the current deficiencies of these guidelines, it will be important to determine the acceptable rate of false-positives in order to prevent a single true-positive. Abstract : Supplemental Digital Content is available in the text